Hydroelastic vibrations of the covers on water turbines with the upper ring of The guide vanes - Мисюра, Сергей Юрьевич (Eastern-European Journal of Enterprise Technologies, 2015)
The paper presents a method of numerical study of hydroelastic vibrations of the covers on water turbines with the upper ring of the guide vanes. We have obtained five natural frequencies and mode shapes of cast iron and steel covers on water turbines with the upper ring of guide vanes in vacuum and with account for the effect of water. In vacuum, the cover of the first-type cast iron has the first natural frequency of 17.3 Hz, while water effect decreases it to 16.9 Hz, which is 2.3 % lower than the frequency in vacuum. The second-type cast iron has the first natural frequency of 14.2 Hz in vacuum, while water effect decreases it to 13.9 Hz, which is 2.1 % lower than the frequency in vacuum. The same variant of cover has been similarly researched with the influence of the steel upper ring of the guide apparatus. The first-type cast iron has the first natural frequency of 15.3 Hz in vacuum, while water effect decreases it to 14.0 Hz, which is 9 % lower than the frequency in vacuum. The ring effect reduced the first natural frequency in vacuum by 13 %, while water effect made it lower by 20.7 %. The second-type cast iron has the first natural frequency of 14.0 Hz in vacuum, while water effect decreases it to 13.4 Hz, which is 4.2 % lower than the frequency in vacuum. The ring reduces the first natural frequency in vacuum by 1.4 %, while the effect of water lowers it by 3.7 %. It is proved that the influence of water and the presence of the ring reduce the frequency of the natural vibrations.